Increased Prevalence of Blood Pressure Instability Over Twenty-Four Hours in Chronic Spinal Cord Injury - Siqi Wang; Jill M. Wecht; Beatrice Ugiliweneza; Bonnie Legg Ditterline (Neurotrauma Reports, 2022)
Spinal cord injury (SCI) leads to cardiovascular dysregulation, including persistent low blood pressure (BP), orthostatic hypotension, and autonomic dysreflexia, leading to daily BP instability that may not be adequately recognized. We compared mean systolic BP, diastolic BP, and heart rate from awake and asleep measurements over a 24-h period among persons with chronic SCI (n?=?33; 30 cervical injuries and three upper thoracic injuries), ambulatory/non-injured (Ambulatory-NI; n?=?13), and non-injured (NI) in a wheelchair (n?=?9). Stability of awake BP was evaluated by deviation of systolic BP from 115?mmHg and percent of systolic BP measurement within and outside of 90?140?mmHg. Variability over 24?h was compared using coefficient of variation and average real variability. Awake hyper- and hypotensive events (change in systolic BP ?20?mmHg from the median) were compared to symptoms reported by the participants corresponding to BP events. Participants with SCI had a lower percentage of awake systolic BP measurements within 90?140?mmHg than Ambulatory-NI and a greater deviation below 115?mmHg. Coefficient of variation and successive differences of awake systolic and diastolic BP were greater in SCI than Ambulatory-NI. Finally, all SCI participants had hyper- and/or hypotensive events and 88% experienced the BP events asymptomatically. In conclusion, participants with SCI had significantly greater BP instability compared with NI, with many hyper- and hypotensive events occurring without symptoms. Clinical management of BP instability, regardless of symptoms, should be a priority after SCI to reduce the risk of cardiovascular disease and improve quality of life.